2020
DOI: 10.3390/cells9020412
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte Infection during Rabies Encephalitis Depends on the Virus Strain and Infection Route as Demonstrated by Novel Quantitative 3D Analysis of Cell Tropism

Abstract: Although conventional immunohistochemistry for neurotropic rabies virus (RABV) usually shows high preference for neurons, non-neuronal cells are also potential targets, and abortive astrocyte infection is considered a main trigger of innate immunity in the CNS. While in vitro studies indicated differences between field and less virulent lab-adapted RABVs, a systematic, quantitative comparison of astrocyte tropism in vivo is lacking. Here, solvent-based tissue clearing was used to measure RABV cell tropism in i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 58 publications
1
62
0
Order By: Relevance
“…We therefore hypothesized that infection in this area may be involved in aggressive behaviors that are frequently observed in humans and animals infected with RABV [58,59]. In order to obtain clues for elucidation of the pathogenic mechanisms of rabies, in the near future, we will exhaustively compare distributions of cells infected with the Koma, 1088 and RABV-Dog strains in mouse brains, by using a 3D imaging technique that was reported recently [24,60].…”
Section: Discussionmentioning
confidence: 99%
“…We therefore hypothesized that infection in this area may be involved in aggressive behaviors that are frequently observed in humans and animals infected with RABV [58,59]. In order to obtain clues for elucidation of the pathogenic mechanisms of rabies, in the near future, we will exhaustively compare distributions of cells infected with the Koma, 1088 and RABV-Dog strains in mouse brains, by using a 3D imaging technique that was reported recently [24,60].…”
Section: Discussionmentioning
confidence: 99%
“…Except for genetically modified mice expressing human angiotensin-converting enzyme 2 (ACE2) [39], the presence of SARS-CoV-2 antigen in animal or human brain samples has yet to be shown. Previous studies with other viral pathogens demonstrated that volumetric 3D imaging using TOC and LSFM is a highly valuable tool to assess the comprehensive distribution of virus infection in vivo [49,52]. Additional immunostaining against tissue-specific cell markers may further facilitate the investigation of the global SARS-CoV-2 cell tropism in affected tissues.…”
Section: Discussionmentioning
confidence: 99%
“…in light sheet fluorescence microscopy (LSFM) (reviewed in [48]). Lately, the opportunities and advantages of TOC for virus research have been demonstrated in several studies [4954]. While two approaches to 3D imaging of SARS-CoV-2-infected lung tissue have been described recently [55,56], neither of them is capable of direct visualization of SARS-CoV-2 infection via virus-specific antigen staining.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of efficient full-genome cloning techniques opened novel avenues for the analysis of virus variability in combination with phenotypical characterization of recombinant field viruses at a clonal level [ 44 ]. For example, a recent comparison of field and lab RABV clones in mice revealed that field viruses not only showed a higher virulence compared to lab strains CVS-11, ERA and SAD L16 but also substantially differ from these viruses in their ability to establish infection in non-neuronal astroglia in the central nervous system (CNS) [ 49 ]. In contrast to attenuated lab-adapted RABV, which is supposed to be eliminated from infected glial cells (astrocytes) by type I interferon-induced immune reactions [ 47 ], it has been hypothesized that rapid onset of field virus gene expression in non-neuronal astrocytes blocks inhibitory innate immune activation and responses [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…So far, technical limitations in conventional histology to visualize infection processes in complex tissues in large three-dimensional (3D) volumes at a mesoscopic scale and high resolution hindered a comprehensive overview of RABV cell tropism, in vivo spread, and pathogenesis. Immunofluorescence-compatible tissue clearing iDISCO and uDISCO (immunolabeling-enabled and ultimate three-dimensional imaging of solvent-cleared organs, respectively) protocols [ 46 , 50 ] recently allowed us to perform high-resolutions 3D immunofluorescence analyses of thick RABV-infected tissues slices [ 49 , 70 ].…”
Section: Introductionmentioning
confidence: 99%